2012
DOI: 10.5424/fs/2012213-02262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pruning in Monterrey Pine Plantations Affected by Fusarium circinatum.

Abstract: Fusarium circinatum Nirenberg and O'Donnell (1998) is the causal agent of Pitch Canker Disease (PCD) in Pinus species, producing damage to the main trunk and lateral branches as well as causing branch dieback. The disease has been detected recently in northern Spain in Pinus spp. seedlings at nurseries and in Pinus radiata D. Don adult trees in plantations. Fusarium circinatum seems to require a wound to enter the tree, not only that as caused by insects but also that resulting from damage by humans, i.e. mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…For other pathogens, results of pruning have not been so positive. Pruning increased F. circinatum canker symptoms in P. radiata plantations in Cantabria, Spain, which was attributed to the role of pruning wounds in permitting the pathogen to infect the tree (Bezos et al, 2012). Pruning increased D. pinea infection in P. radiata trees in New Zealand that were experimentally inoculated, with a large increase in infection rates with intensity of pruning (percentage of crown removed; Chou and MacKenzie, 1988).…”
Section: Pruning and Coppicingmentioning
confidence: 99%
“…For other pathogens, results of pruning have not been so positive. Pruning increased F. circinatum canker symptoms in P. radiata plantations in Cantabria, Spain, which was attributed to the role of pruning wounds in permitting the pathogen to infect the tree (Bezos et al, 2012). Pruning increased D. pinea infection in P. radiata trees in New Zealand that were experimentally inoculated, with a large increase in infection rates with intensity of pruning (percentage of crown removed; Chou and MacKenzie, 1988).…”
Section: Pruning and Coppicingmentioning
confidence: 99%
“…Disease severity is greater in coastal than inland locations in the US, and has been ascribed, among other factors, to longer periods of free moisture on host surfaces owing to frequent intervals of fog in the coastal zone [66]. A similar coastal effect was described also in Northern Spain [67,68] and confirmed by a species distribution model developed for PPC in Spain [69][70][71]. According to this model, only distance to the coast, precipitation, and temperature were significant variables explaining the PPC dispersal.…”
Section: Biology and Ecology Of The Pathogenmentioning
confidence: 85%
“…Gordon et al [129] recommended carrying out pruning operations during cool and dry periods to minimize the risk of infection. Bezos et al [67] found more dead trees in unpruned plots than in pruned ones, which was related to the decrease of the quantity of inoculum in the air and surrounding trees due to pruning and wood removal.…”
Section: Other Pathways Of Spreadmentioning
confidence: 99%
See 2 more Smart Citations